Thyroid gland neoplasms; histopathological pitfalls as a consequence of FNAC: a tertiary care hospital experience - Pyarali, Maheen; Uneeb, Saher; Adeel, Maira; Aqil, Shakil; Zahid, Yousra (Journal of the Pakistan Medical Association, 2022)
Fine-needle aspiration cytology (FNAC) is one of the useful procedures for the investigation of thyroid swellings. FNAC is a minimally invasive procedure, is cost effective, and a gold standard for diagnosing thyroid lesions. Haemorrhage, thrombosis, and infarction are known common complications of FNAC. Post FNAC infarction in thyroid gland has been known as a rare phenomenon. Here, we report the case of a young female who underwent FNAC that showed Hurthle cell neoplasm (Bethesda 3). Four weeks later, she underwent right thyroid lobectomy and the final histology showed extensive necrosis and haemorrhage which is a diagnostic dilemma and hampered our diagnosis. Keywords: Hurthle cell neoplasm, FNAC, Thyroidectomy, Thyroid neoplasm.